The witches of Eastwick [videorecording (DVD)] - Miller, George, 1945 March 3-; Nicholson, Jack; Cher, 1946-; Sarandon, Susan, 1946-; Pfeiffer, Michelle, 1957-; Updike, John (Distributed by Warner Home Video, 2006)
Three witches conjure up the perfect man for their lives, not knowing that he is really the devil himself.